Academic Supervision for Salafiyah Islamic Boarding Schools - Dendi Azim; Wido Supraha; Abdul Hayyie Al Kattani (al-Afkar, Journal For Islamic Studies, 2024)
The variety of systems and policies offered by educational institutions in Indonesia shows that there are innovative practitioners in terms of education in Indonesia. Some of these institutions have been established classically and traditionally, one of which is the pesantren. The orientation of Islamic boarding schools in building the character strength of generations based on spiritual qualities is an offer that is much needed in the current era of globalization. The purpose of writing this thesis is to be able to find out how the practice of implementing academic supervision for salafiyah Islamic boarding schools at Nurul Hidayah Sadeng Islamic Boarding School, Central Bogor, the academic supervision model applied to salafiyah Islamic boarding schools, and formulate what methods are good and good to use at salafiyah Islamic boarding schools. This study uses a qualitative approach. In the form of research that produces descriptive data in the form of categories, characteristics, or certain characteristics. Pondok Pesantren Nurul Hidayah Pusat is one of the largest and leading salaf-based Islamic educational institutions in West Bogor. The Islamic boarding school founded by KH. Uqon Bulqoeny in 1959M is located on Jl. KH. Mama Bakry Kp. Sadeng Kaum Rt.05/02 Des.Sadeng Kec. Leuwisadeng Regency. Bogor. The academic supervision method used by the principal at Pondok Pesantren Nurul Hidayah uses a collaborative approach, namely direct and indirect approaches. The supervision technique used uses two techniques, namely individual techniques and group techniques. Individual techniques include: class visits, individual observations and meetings. Group techniques by holding teacher meetings and training to improve teacher competence. In supervising the head of the madrasah or the leadership of the pesantren, it is better to apply more varied, efficient and innovative academic supervision methods and techniques so that they can be used to improve the quality of teaching and learning activities in Islamic boarding schools in particular.